Scientific Tafsir and Oceanographic Stratification: Barzakh in Zaghloul El-Naggar’s Hermeneutics - Raodah Raodah; Sarwadi Sarwadi; Nur Hayati (JURNAL ISLAM NUSANTARA, 2025)
This study explores the relationship between the Qur'an and modern science, particularly through Zaghloul El-Naggar's tafsīr' ilmī (scientific exegesis) of the concept of barzakh in Surah Ar-Rahman: 19-20. El-Naggar correlates the Qur'anic description of the barrier between two seas with the scientific theory of density stratification in oceanography. The research employs a qualitative library research method, applying a hermeneutical framework to critically analyze the epistemological and methodological aspects of El-Naggar's interpretation. The findings reveal that while El-Naggar's approach effectively integrates scientific phenomena with religious texts, it risks oversimplifying the Qur'an’s metaphysical and theological meanings by relying too heavily on empirical validation. The study contrasts this with al-Tantawi Jawhari's more spiritual hermeneutics, which emphasizes moral and reflective aspects of natural phenomena. The research contributes to the Development of a balanced tafsīr' ilmī approach that harmonizes scientific inquiry with spiritual reflection, offering valuable insights for contemporary Islamic education and the integration of science and religion. Future research could further explore diverse tafsīr' ilmī approaches and expand the empirical scope to deepen understanding of the Qur'an’s relationship with science